Peran Kebijakan Lingkungan dan Faktor Industri dalam Mendorong Kinerja Keuangan Perusahaan melalui Manajemen Akuntansi Lingkungan - Surijadi, Herman; Balik, Dessy (Program Studi Administrasi Niaga STIA Said Perintah, 2024)
This study examines the influence of government environmental policies and industry factors on corporate financial performance through the implementation of Environmental Management Accounting (EMA). Employing a quantitative approach, this research utilizes survey methods with purposive sampling, focusing on companies operating in Indonesia that have adopted EMA practices and publicly disclose their financial statements. Data were collected from corporate financial reports and annual reports listed on the Indonesia Stock Exchange (BEI) and companies participating in the PROPER program from 2018 to the present. The analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to test the relationships between variables.